Applications of IoT technology for climate change adaptation in the Mekong Delta - Vinh Quoc Danh Luong (CTU Journal of Innovation and Sustainable Development)
The Mekong Delta, with an area of over 40,000 square kilometers, is the largest agricultural and fishery production center in Viet Nam. However, along with the Ganges River Delta and the Nile River Delta, the Mekong Delta is one of the three delta regions most severely impacted by climate change. In recent years, this region has faced drought, saltwater intrusion, environmental degradation, and land subsidence mainly caused by climate change. The Internet of Things (IoT) technology has been envisioned as a powerful tool for combating climate change. This paper presents some research projects that leverage the potential of IoT technology and applications to improve the effectiveness of rice cultivation and aquaculture; and support the development of riverbank landslide early warning systems for the region. Through these applications, IoT technology has provided practical answers to address climate change and save the environment.